Exploring Radicalisation Phenomenon Among Muslims in Ghana: Challenges And Prospects - Yahuza, Nurul-Haqq; Kabuye Uthman Sulaiman; Ahmad El-Muhammady Bin Uthman El-Muhammady (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Radicalisation is a phenomenon that advocates and promotes violence related with or justified by specific ideological, political, social, or religious views. Conflicts is the major engine of these violent extremism and radicalisation, with nations participating in a violent conflict or witnessing high levels of political terror. This has accounted for more than 99 percent of all terrorist related deaths. The acts of terrorism and violent extremism are confronting reality in the globe and an ongoing threat in Ghana and beyond. The study focuses on radicalisation and violent extremism, i.e. youth involvement in engaging in terrorism activities in Ghana. It explores the root causes of radicalisation, ideological factors, socio-economic systems, and external (regional and international) factors to radicalisation and violent extremism. The study also seeks to understand the counter measures adopted by the government to address the issues and evaluates its strength and weaknesses in order to propose improvement. The following factors are presented against the background that youth radicalisation in Ghana is an increasing phenomenon, and a better knowledge of the process and the elements involved with radicalisation and youth membership in violent extremist organizations is required. The methodology employed was qualitative, hence interviews were conducted. The findings show that the major challenges to radicalisation in Ghana were the case of unemployment and the influx of audio tapes /videos of Nigerian scholars into the Ghanaian Islamic mainstream media/Saudi graduates. Other challenges that were also identified by respondents as elements that drives Muslim youths towards radicalisation included extreme love for religious leaders. It was suggested that in order to solve the issue of radicalisation, there should be programs that aims at promoting dialogue and reconciliation among Muslims in Ghana, and also eeliminating all forms of extremist ideologies. again, educating Muslims in Ghana on what Islam says about radicalisation and the dangers associated with it.